2018
DOI: 10.1021/acs.cgd.7b01552
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Elimination of Anti-site Defects during Crystallization in Perovskite Ba1–xSrxLiF3

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…is an anion conductor (Kamata et al, 1998;Rush et al, 2001) and precludes lithium ions from playing a role in long-range transport. Any mobility of these (Dü vel et al, 2010(Dü vel et al, , 2018 would be confined to anion vacancies, antisite defects or surfaces (Kunkel et al, 2014). As these findings are founded on purely geometrical considerations (including ionic radii), they are valid not only for BaLiF 3 but also for all perovskites with similar ratios of ionic radii, i.e.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…is an anion conductor (Kamata et al, 1998;Rush et al, 2001) and precludes lithium ions from playing a role in long-range transport. Any mobility of these (Dü vel et al, 2010(Dü vel et al, , 2018 would be confined to anion vacancies, antisite defects or surfaces (Kunkel et al, 2014). As these findings are founded on purely geometrical considerations (including ionic radii), they are valid not only for BaLiF 3 but also for all perovskites with similar ratios of ionic radii, i.e.…”
mentioning
confidence: 69%
“…A variety of structural bulk defects in BaLiF 3 have been computed and discussed, amongst them LiF pseudo-Schottky defects as the thermodynamically most stable (Jackson et al, 1996). However, more recent studies indicate that cation antisite defects, according to equation (1) (Zahn et al, 2011;Dü vel et al, 2018), and fluoride-oxide substitution (from water vapour or carbon dioxide), according to equation (2) (Jackson & Valerio, 2002;Qiao et al, 2009), are the most common intrinsic and extrinsic defects, respectively:…”
Section: Introductionmentioning
confidence: 99%
“…While there is ongoing scientific and commercial interest in BaLiF 3 (e.g., most recently as host for luminescent lanthanoid and actinoid ions and as antisite defect material), less attention is paid to BaLiH 3 – probably because of its air sensitivity. [Understandably, the more expensive BaLiD 3 was only used for sparse neutron diffraction/scattering studies connected to structure elucidation and luminescence of guest europium(II) ions …”
Section: Introductionmentioning
confidence: 99%
“…However, the preparation of materials with a low antisite defect density can be challenging. (6)(7)(8)(9) The formation of cation antisite defects was recently investigated in case of perovskite-type Ba1-xSrxLiF3 using molecular dynamics (MD) simulations (12) . It was found that the growth of perovskite-structured BaLiF3 goes along with Ba ions commonly crystallizing onto Li sites and Li ions onto Ba sites.…”
mentioning
confidence: 99%
“…However, a few wrongly crystallized cations become trapped in the crystal, creating Ba-Li antisite defects. (12) Ball milling is a simple solvent free method of preparing functional materials, with different defect structures compared to thermally synthesized materials. (13,14) It can be used to prepare materials that cannot be prepared thermally, such as solid solutions within miscibility gaps.…”
mentioning
confidence: 99%